The Effect of Good Corporate Governance, Intellectual Capital, Firm Size, and Company Growth on Company Profitability - Fransisca Pauliena Roslynwibowo; I Wayan Suartana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The property and real estate sector is one of the business sectors that makes a significant contribution to the country's economic turnover and growth. With the ever-evolving challenges, companies in the property and real estate sector must adapt their business strategies to remain competitive amidst uncertain market conditions. Therefore, innovation in resource management and efforts to enhance operational efficiency are essential to drive optimal profitability. This study aims to examine the effect of good corporate governance, proxied by the board of directors and audit committee, intellectual capital, firm size, and company growth on company profitability. This research utilizes secondary data sourced from the annual reports of property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The sample was selected using a purposive sampling method based on specific criteria, resulting in a total of 50 companies as observations. The collected data were analyzed using SPSS software with a multiple linear regression method. The results indicate that the board of directors, audit committee, intellectual capital, and company growth do not have a significant effect on company profitability, whereas firm size has a positive and significant effect on company profitability.